Identification and phylogenetic analysis of carbapenemase genes from clinical strains of Klebsiella pneumoniae - Kaboré, Boukaré; Ouédraogo, Ganamé A; Ouédraogo, Henri S; Cissé, Hama; Zongo, Oumarou; Zongo, Koudbi J; Zeba, Boukaré; Sanou, Idrissa; Savadogo, Aly (The Journal of Infection in Developing Countries, 2024)
Introduction: Klebsiella pneumoniae is an encapsulated Gram-negative bacterium that is responsible for numerous infections in healthcare facilities worldwide and is frequently isolated. The World Health Organization has listed K. pneumoniaeas as a critical antibiotic resistant bacterial pathogen for which new antibiotics are urgently needed. This study aimed to use molecular tools to identify and examine antibiotic resistance in clinical strains of K. pneumoniae. Methodology: A total of 15 unduplicated K. pneumoniae strains isolated from patient samples with multidrug-resistant (MDR) profiles were subjected to polymerase chain reaction (PCR) to amplify the most common carbapenem resistance genes. (GTG)5 PCR and phylogenetic analysis were performed to identify the genetic relationship between the strains. Results: All strains yielded a (GTG)5-PCR profile, and this allowed us to group these strains into 8 groups according to the size and number of characteristic bands. Phylogenetic analysis was done using the free software UPGMA and a single bacterial clone with a correlation coefficient of over 97% was identified. New Delhi metallo-beta-lactamase NDM-like (blaNDM) carbapenem resistance genes were detected in three strains of K. pneumoniae, which represented a resistance rate of 20%. However, carbapenemases type A [Klebsiella pneumoniae carbapenemase (KPC) and imipenem-hydrolysing beta-lactamase (IMI), type D [oxacillinase-48 (OXA-48)], and other metallo-β-lactamase [Verona integron-encoded metallo-beta-lactamase (VIM), and enzyme active on imipenem (IMP)] were not detected. Conclusions: We identified and grouped the blaNDM resistance genes of Klebsiella pneumonia strains.